PENGARUH PEMBELAJARAN AKTIF TIPE BELAJAR DIMULAI DARI PERTANYAAN (LEARNING START WITH A QUESTION) TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII SMPN 1 LEMBAH GUMANTI KAB. SOLOK - Sukma, Sherly Herawita; Ardi, Ardi; Nursyahra, Nursyahra (STKIP PGRI Sumbar, 2013)
ABSTRACT The purpose of this research was to know the effect of applying active learning type learning start with a question (LSWQ). Kind of this research was experimental research. The design of the research was randomized control group only design with the population of the grade VII students of SMPN 1 Lembah Gumanti Kabupaten Solok that consisted of six classes. The technique of taking sample done with purposive sampling so it got the result VIIC as experimental class and VIID as control class. The instrument used was post test with objective test form. The data analysis was done with ttest. Based on the test score of the learning result student biology got the mean score of experimental class (76,44), hinger than control class (68,99). From the data analysis got ttest was (1,850) than ttable (1,680). Because ttest > ttable so the hypotesis was accepted. It can be concluded that, active learning type learning start from question got significance students learning biology result at the grade VII student of SMPN 1 Lembah Gumanti Kabupaten Solok.